VARIETY AS A FACTOR OF FORMING STABLE AGROCENOSES OF GRAIN CROPS - Mostoviak, I. I.; Demyanyuk, O. S.; Parfenyuk, A. I.; Beznosko, I. V. (Scientific Progress & Innovations, 2020)
The necessity of manufacturing high quality crop growing products and increasing ecological safety of agrocenoses requires solving a number of urgent scientific problems, in particular, connected with interac-tion of phytopathogenic micromycetes’ populations with a variety of cultivated plants. Therefore, the aim of our research was to determine ecologically stable varieties of cereals, which are characterized by group re-sistance to phytopathogenic fungi. Seed samples of modern varieties of grain cereal crops were analyzed – winter wheat, spring barley and oats – as to their contamination with phytopathogenic micromycetes. Spe-cies composition of micromycetes has been determined and it has been found that the seeds of the most of the studied cereal crop varieties are contaminated with phytopathogenic fungi of Alternaria, Fusarium, Ni-grospora, Bipolaris, Penicillium, Mucor, Epicoccum, Glicocladium, Drechslera genera with high intensity of spore formation, which is ecologically dangerous for agrocenoses and causes the development of plant fun-gal diseases. The intensity of spore formation has been determined and pathogens from cereal crop seeds have been isolated. It has been shown that the spectrum and number of phytopathogenic fungi largely de-pend on the variety where spore concentration varied from 0.1 to 10 million pcs/ml. It has been established that Aurora Myronivska, Podolianka winter wheat varieties, MIP Sharm spring barley and Skarb Ukraiiny oats are characterized by the smallest species diversity of phytopathogenic fungi with low intensity of their spore formation and can be recommended for cultivation. It is known that pathogenic microflora causes sig-nificant losses of grain yield and reduces its quality, and under improper storage conditions – reduces the sowing quality of seeds. So quality indicators of cereal crop seeds (winter wheat, spring barley and oats) have been determined: germination energy, laboratory germination and infection of seeds with pathogenic microbiota; also the connection between these indicators has been revealed. According to the results of the study, it has been shown that high level of infection of cereal crop seeds with fungal pathogens reduces the sowing quality of seed material by 80%. It has been proven that it is necessary to evaluate crop varieties as a factor of forming stable and ecologically safe agrocenoses, which will enable to control the stability of agro-ecosystems in space and time and obtain environmentally safe crop growing products.